Post Enumeration Survey of the 2001 Portuguese Population and Housing Censuses - Pedro Simões Coelho; Fernando Casimiro (Revstat, 2008)
Within the framework of the quality control and evaluation program for the Portuguese 2001 Census, the Portuguese statistical office (INE) conducted a Post Enumeration Survey (PES) to measure quality. The main aims of the PES were to evaluate coverage errors and content errors for the target populations. The PES is a probabilistic sampling survey representative at NUTS II level. This paper describes the methodology for this survey. The paper includes a discussion of sample size and allocation resulting from the imposition of maximum coefficients of variation for a set of variables both at regional and national level. The methodology used to obtain predictions for resident populations and dwellings is also presented. These predictions are used in the definition of inclusion probabilities for the primary sampling units. The sampling design is finally compared with two alternative designs (with a smaller number of stages), concluding for the advantage of the proposed design in regard to the survey goals.